Pleioblastus triangulata (Poaceae: Bambusoideae), a new combination for Indosasa triangulata based on morphological and molecular evidence - Niu, Zheng-Yang; Tong, Yi-Hua; Xia, Nian-He (Phytotaxa, 2021)
This study aims to end the debate whether Indosasa triangulata belongs to Indosasa or Pleioblastus. The evidence from our morphological study and molecular phylogenetic analyses clearly indicate that Indosasa triangulata should be a member of Pleioblastus, rather than Indosasa, and is a distinct species close to Pleioblastus maculatus and P. oleosus. Thus, it is transferred from Indosasa to Pleioblastus in this study. A detailed description as well as two color plates of this species is also provided.